A case report of stellate ganglion block in the treatment of epileptic pain. Issue 6 (February 2017) - Wang, Shengtao; Zhu, Yangzi
Abstract: Rationale: Stellate ganglion blocks have been shown to provide effective pain relief in a number of different conditions, but no one had reported stellate ganglion blocks for the treatment of epileptic pain. We describe a case report of the successful use of stellate ganglion block in the treatment of epileptic pain in the patient. Patient concerns: A 8-year-old girl who had experienced severe paroxysmal pain in her right upper limb. Diagnoses: She was diagnosed as drug-resistant partial epilepsy. Interventions: The patient received stellate ganglion blocks with lidocaine for 2 courses with 2 weeks in a course of treatment and oral carbamazepine once a day. Outcomes: Carbamazepine dosage gradually tapered until stop and epileptic pain attacks become less and less, eventually disappear. Lessons: Stellate ganglion block may be an effective treatment of intractable partial epilepsy. However, more research is now needed to verify the validity.